Development of a novel multiplex PCR for detection of Brucella, Leptospira and Bovine herpesvirus-1 - BHURE, S K; CHANDAN, S; AMACHAWADI, R G; PATIL, S S; SHOME, RAJESWARI; GANGADHAR, N L; GAJENDRA, M R; PRABHUDAS, K (The Indian Journal of Animal Sciences, 2012)
A novel multiplex PCR (mPCR) was developed for detection of Brucella, Leptospira and bovine herpesvirus-1 (BoHV-1) targeting conserved regions of BCSP31, LipL32 and gB genes, respectively. No template controls were also run with each test. Electrophoresis of mPCR products showed bands specific to genus Brucella, Leptospira and BHV- 1, respectively. The assay detected as low as 15 pg of each template. The mPCR showed specific bands with 4 Brucella species, 14 pathogenic Leptospira serovars, BoHV-1. In addition, 10 (out of 135 bull semen samples) and 5 (out of 17 bovine blood samples) showed a ~640bp amplicon specific to brucellosis. Five human urine samples were tested; 3 found positive for Leptospira and other 2 were positive for both Leptospira and Brucella. The assay is accurate, specific and cost effective tool for detection of Brucella, Leptospira and bovine herpesvirus-1 and will also be a valuable tool for the diagnoses of co-infection. The assay could be a preferable detection methodology for routine screening and molecular epidemiology of brucellosis, leptospirosis and infectious bovine rhenotracheitis.